PERAN PUBLIC RELATIONS DALAM KOMUNIKASI BISNIS DI ERA MODERN - Aurahman, Sifa; Muhammad Rif’an; Abdul Muhyi; Dwi Novaria Misidawati (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The development of digital technology has transformed how organizations communicate with their publics, requiring Public Relations (PR) to be more strategic and adaptive. This study uses a descriptive qualitative approach through literature review to analyze the role of PR in modern business communication. The findings show that PR plays a key role in building corporate image and reputation, managing digital information, utilizing social media for two-way interaction, and responding quickly to issues and crises. PR also contributes to strengthening branding and maintaining relationships with both internal and external stakeholders. The digital era demands that PR practitioners possess data analysis skills, content creativity, and an understanding of communication technology. Overall, PR becomes an essential element in maintaining credibility and ensuring business sustainability within a rapidly changing communication environment.